A phenomenological exploration of counselling students’ experiences with group counselling sessions - Ng, Jia Wei (2023)
Problems such as counsellors doubting their own abilities and incompetency even lead to the situation where group counsellors are reluctant to conduct group counselling sessions. This study aims to explore the experience of group counselling sessions from the perspective of counselling students. The research question is to understand the phenomenon of counselling students in group counselling by asking sub-questions about their attitudes towards group counselling, the characteristics of counselling students in group counselling sessions, and the impact of group counselling among them. This research applied phenomenology design by conducting a semi-structured interview. It involves six counselling students who are currently studying the guidance and counselling programme at Universiti Tunku Abdul Rahman (UTAR) Kampar, using the purposive sampling method. With the application of qualitative methodology, this study is able to provide a more in-depth exploration of the experiences with group counselling when the participants had carried out at least one complete group counselling session independently with fundamental knowledge. There is a scarcity of literature related to the experience of group counselling students, especially in the Malaysian context. This study also explores the experiences with a new perspective, using the counselling theory of Gestalt therapy as the theoretical framework. Consequently, the findings are also beneficial for students who are involved in group counselling and for counsellor educators to get updated research about group counselling topics. It shows that the students who are currently still studying the counselling programme have awareness about the way they reflect themselves through group counselling but low awareness when it comes to their competency. This research fills the knowledge gap by studying from the perspectives of counselling students, who are still on the path to becoming a professional counsellor.